A função ϕ de Euler e aplicações na criptografia RSA - Pacheco, Karen Stephane Nogueira (2024)
This research deals with the relationship between Number Theory and Cryptography, specifically to the study of Euler's ϕ-Function and its application in RSA Cryptography. Historical and preliminary aspects of RSA Cryptography will be presented, as well as some definitions and theorems that are necessary for understanding the Euler Function and, finally, properties, the calculation of the function and some calculation examples followed by some application of the function in RSA cryptography.